Efficient separation of magnesite and quartz using eco-friendly Dimethylaminopropyl lauramide experimental and mechanistic studies. (October 2022) - Zhao, Panxing; Liu, Wenbao; Liu, Wengang; Tong, Kelin; Shen, Yanbai; Zhao, Sikai; Zhou, Shijie
Highlights: 1. An eco-friendly and economic surfactant DPLA was introduced as a collector in flotation separation of quartz-magnesite system. 2. DPLA exhibited excellent flotation performance to quartz than magnesite. 3. The adsorption mechanisms of DPLA on quartz and magnesite were analyzed. 4. Electrostatic force and hydrogen bonding interaction caused the adsorption of DPLA onto the quartz surface. Abstract: To achieve efficient separation of magnesite from quartz, a novel cationic collector—Dimethylaminopropyl lauramide (DPLA), was introduced into the quartz-magnesite reverse flotation system. The flotation performance and adsorption mechanism of DPLA on the minerals surfaces were investigated by micro-flotation tests, contact angle measurements, zeta-potential measurements, Fourier transform infrared spectroscopy (FTIR) analysis, Atomic force microscope (AFM), and Density functional theory (DFT) calculation. The single mineral micro-flotation results showed that when DPLA concentration was 25 mg/L, 94.6% of quartz was removed and 97.14% of magnesite was recovered under natural pulp pH. Further, the artificial mixed mineral flotation results demonstrated that DPLA had a superior selectivity for quartz and the concentrate with 44.36% MgO grade and 98.69% MgO recovery was obtained at 25 mg/L DPLA, and the separation efficiency was 89.52%. Contact angle measurement results suggested that the hydrophobicity of quartz surface increased significantly after treatment with DPLA and indicated the interaction between DPLA and quartz was stronger than that with magnesite. The results of zeta-potential measurements, FTIR, AFM, and DFT calculation revealed that the adsorption of DPLA on the quartz surface was mainly by the electrostatic force and hydrogen bonding interactions. In addition, the advantages of DPLA as the collector were analyzed in terms of environmental aspects and economics. DPLA has great potential for industrial application to effectively separate magnesite from quartz.